Pengembangan Bahan Ajar IPAS Berbasis Kearifan Lokal Suku Mbojo untuk Materi “Indonesiaku Kaya Budaya” Kelas IV Sekolah Dasar - Fitriani; Muhammad Sobri; Hikmah Ramadhani Putri (Mataram University, 2026)
The development of teaching materials in Science and Social Studies (IPAS) learning requires a contextual approach to help students understand material on cultural diversity. This study aims to develop teaching materials based on the local wisdom of the Mbojo Tribe for IPAS Chapter 6 “My Indonesia is Rich in Culture” for grade IV students of SDN Inpres 1 Wora, and to determine their validity and practicality. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 23 grade IV students of SDN Inpres 1 Wora, consisting of 8 students in the small-group trial and 15 students in the large-group trial, along with one classroom teacher. Data were collected using interviews, observation, and questionnaires, comprising a material-expert validation questionnaire, a media-expert validation questionnaire, a teacher-response questionnaire, and a student-response questionnaire. Quantitative data were analyzed using the percentage formula P = (Σx/Σxi) × 100%, while qualitative data in the form of suggestions from the validators were analyzed descriptively as a basis for product revision. The resulting product is a full-color printed book integrating IPAS material with the local wisdom of the Mbojo Tribe, covering customs (Uma Lengge, Rimpu, Genda), traditional games (Mpa'a Gantao, Mpa'a Ndempa Ndiha), and traditional foods (Mangge Mada, Uta Palumara Londe). Validation results show the teaching material is in the very valid category, with a media-expert score of 97% and a material-expert score of 96%. It is also very practical, based on student responses in the small-group (95%) and large-group (96%) trials, and teacher responses (100%). The teaching material is therefore considered suitable for grade IV IPAS learning and contributes to the preservation of local culture.